Analisis Struktur dan Jenis Kalimat Teks Eksposisi Dalam Buku Siswa Kelas X SMA - Salsabilla Layya; Ridwan Ibrahim; Armia Armiya (JIM Pendididikan Bahasa dan Sastra Indonesia, 2021)
This study entitled Structure Analysis and Sentence Types of Exposition Text in Class X SMA Student Books. Thhe formulationnjyf of the problemss in thiss studyy, namely (1) howw iis thee structure of the exposition text in the textbooks of class X SMA students, and (2) what are the types of exposition text sentences in the textbooks of classs X SMA students. This study aims, (1) to desscribe the structure of the exposition text in the textbooks of classs X SMA students, and (2) the types of exposition text sentences in the books of classs X SMA students. Thiis reesearch is useful for researchers, teachers, and students. For researchers, this study can add insight and direct experience in analyzing the structure and types of sentences in the exposition text and can be a reference for future researchers. For teachers, the results of this study can increase knowledge about how to analyze and can be a reference in planning lessons regarding the text of the exposition. For students, this reesearch caan bee useed to study the structure and types of sentences in the exposition text specifically so as to improve students' skills in understanding the structure and types of sentences in the exposition text. This research method uses a qualitative approach with descriptive research type. The data of this research are in the form of structure and types of sentences in the text of the exposition. The data source of this research is the exposition text in the textbooks of class X SMA students. The data was collected by reading the exposition text, sorting the number of paragraphs and sentences in the exposition text, marking the strucgture and sentence types of the exposition text, and classifyjying the data into tables. The analyysis tecchnique used in this reesearch is qualitaative analyysis techniiques. The resuglts showehd thaat in the textbook of class X SMA found a complete text structure of the exposition, namely a statement of opinion, a series of arguments, and a conclusion. Types of sentences in the structure of the exposition text include (1) single sentences, (2) equivalent compound sentences, (3) multilevel compound sentences, and (4) mixed compound sentences. The single sentence type is the type of sentence that is mostly found, namely 11 sentences. Types of compound sentences are equivalent to 5 sentences. The smallest type of sentence found was the mixed compound sentence type with a total of 1 sentence. Finally, there is a type of multi-tiered compound sentence, which consists of 2 sentences